Caracterização bromatológica e perfil em ácidos graxos de bebidas lácteas não fermentadas - Amaral, João Batista Silvestre do (2010)
The main objective of this work is to determine the fat acids profile of milk beverages not fermented available in the market of Maceió-AL city. Samples of milk beverage not fermented were acquired in Maceio s market and it were submitted for pH, lipids and protein analysis and fat acids profile by gas chromatographic GC-MS analysis of its methyl esters. The samples shows in the package s nutritional information null trans fat acid contents, and variations on the contents of proteins, total lipids and carbohydrates. The analytic results show that samples pH was between 6,6 and 7,0; the total carbohydrates content between 14,1 and 24,9 g/200mL; the total lipids content changes about 3,7 and 6,3 g/200mL; the proteins content on the range of 2,5 up to 4,9 g/200 mL. The chromatographic analysis shows that more abundant fat acids were C6:0, C8:0, C10:0, C11:0, C12:0, C14:0, C15:0, C16:1n7c, C16:0, C18:2n6c, C18:2n6t, C18:1n9c + C18:1n9t, C18:0. The analytical results disagree from package s nutritional information, the trans fat content is not null, and that food compound presents omega 6, but no omega 3 essentials fat acids.